2016
DOI: 10.11138/jts/2016.4.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture versus microfracture and platelet-rich plasma: arthroscopic treatment of knee chondral lesions. A two-year follow-up study

Abstract: Level II, prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…While functional and clinical outcomes via the visual analogue pain score, Short Form-36, and International Knee Documentation Committee Subjective Knee Form were not significantly different, they were slightly better in the PRP cohort. 16 A similar study from Zedde et al showed continued improvement in terms of pain symptomology and functional improvement when comparing a group of 30 patients who underwent microfracture followed by a series of 3 PRP injections, compared with a group of 30 whom underwent microfracture alone. 16 As promising results such as these continue to be shown, it is possible that the trend toward increasing numbers of microfracture type cartilage procedures and decrease in the number of palliative procedures will continue.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While functional and clinical outcomes via the visual analogue pain score, Short Form-36, and International Knee Documentation Committee Subjective Knee Form were not significantly different, they were slightly better in the PRP cohort. 16 A similar study from Zedde et al showed continued improvement in terms of pain symptomology and functional improvement when comparing a group of 30 patients who underwent microfracture followed by a series of 3 PRP injections, compared with a group of 30 whom underwent microfracture alone. 16 As promising results such as these continue to be shown, it is possible that the trend toward increasing numbers of microfracture type cartilage procedures and decrease in the number of palliative procedures will continue.…”
Section: Discussionmentioning
confidence: 87%
“…While studies examining the longterm results of PRP augmented microfracture are limited, early studies show that the addition of PRP is at least as effective as microfracture alone, if not better, with respect to clinical and functional outcome. 16 Mancò et al performed a prospective study of patients aged 52 years, with 13 being treated with microfracture alone, and 14 undergoing microfracture augmented with PRP. While functional and clinical outcomes via the visual analogue pain score, Short Form-36, and International Knee Documentation Committee Subjective Knee Form were not significantly different, they were slightly better in the PRP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐rich plasma (PRP) contains a high concentration of growth factors, including transforming growth factor‐β (TGF‐β), insulin‐like growth factor (IGF), platelet‐derived growth factor (PDGF), and vascular endothelial growth factor (VEGF). Since the 1990s, PRP has been widely used in tissue lesions and degenerative disorders . Recent clinical studies have demonstrated that PRP administered by intra‐articular injection can provide symptomatic relief and result in functional improvement in patients with mild to moderate knee OA …”
mentioning
confidence: 99%
“…49,[69][70][71][72][73][74][75][76][77][78] MSP can be augmented using cells, biologics, and/or matrices in an attempt to speed and improve defect-tissue fill volume and quality and improve outcomes. 5,15,75,[79][80][81][82][83][84][85] In general, these MSPþ techniques have reported advantages over MSP alone and can be considered for use based on surgeon preference, availability, and cost-effectiveness. The primary limitations associated with MSP and MSPþ techniques involve the size and type of defects that can be effectively treated, the potential sequelae to violation of the subchondral bone plate and dependency on bone marrow-derived cells for repair tissue formation, and the durability of the repair tissue and associated progression of pathology to early-onset knee OA.…”
Section: Marrow Stimulation Proceduresmentioning
confidence: 99%